FACTORS THAT INFLUENCE CONSUMER SATISFACTION: THE ROLE OF CREATIVITY AND PRODUCT INNOVATION FOR SMES IN THE CITY OF BANDUNG - Jeffri Nava Wardana; Radea Respati Paramudhita (SEAN Institute, 2023)
Bandung is one of the tourism cities with a wide variety of handicraft products which are an attraction for tourists. This study aims to determine the factors that influence consumer satisfaction by looking at the role of the creativity of business people and product innovation. In this study, 110 questionnaires were distributed online to consumers in the city of Bandung, West Java. The data were then processed using multiple regression analysis with the help of SPSS 25 software. The results of this study indicate that there is a direct influence between creativity and customer satisfaction. In addition, product innovation also has an effect on consumer satisfaction. The results in this study obtained a score of 54.2%, This score indicates that there is an influence between the variables of creativity and product innovation on customer satisfaction. This study is proposed to emphasize the importance of creativity and innovation skills in product development, especially in the handicraft industry in the city of Bandung